HUBUNGAN PENGGUNAAN KONTRASEPSI DENGAN ASUPAN MAKRONUTRIEN DAN STATUS GIZI PADA WANITA USIA SUBUR (WUS) DI KECAMATAN TEBET - Lusiani Arfini (2023)
Female obesity prevalence was 44.4% higher than male at 26.6% and the most used contraception method is hormonal contraception. There is an evidence of the effect of hormonal contraception to weight gain. This research aims to investigate the relationship of contraceptive use with macronutrient intake and nutritional status, also the differences between users and non-users of hormonal contraception among reproductive-age women in Tebet District using a cross sectional study design with 106 respondents using quota sampling method. The results show no association between hormonal contraception and BMI (p=0.081), waist circumference (p=0.789), intake of energy (p=0.0675), protein (p=0.758), fat (p=0.156), and carbohydrates (p=0.23). There was a relationship between the duration of contraceptive use and waist circumference (p=0.042) but no with BMI (p=0.052). No association between duration of contraceptive use and BMI (p=0.163 and 0.248) also waist circumference (p=0.282 and 0.066) among users and non-users of hormonal contraception. There was a significant difference in BMI (p=0.032) with the non-user group being higher. No significant difference in waist circumference (p=0.195), intake of energy (p=0.941), protein (p=0.541), fat (p=0.371), and carbohydrate (p=0.267). The multiple linear regression shows that only fat and carbohydrate intake was significantly impact with BMI and waist circumference.